АКАДЕМИЯЛЫҚ ЛИЦЕЙЛЕРДЕ Т.ҚАЙЫПБЕРГЕНОВ ДӨРЕТИЎШИЛИГИН ОҚЫТЫЎ МЕТОДИКАСЫ - Юсупов, Қ.А. (FAN va JAMIYAT, 2020)
The article is devoted to the issues of methods of teaching Karakalpak literature, and the creative work of Т.Qayipbergenov, in particular. The author of the article gives recommendations how to organize the problem, review and other types of lecture in the study of the creative work of the famous Karakalpak writers and poets.